2017
DOI: 10.1007/s11524-016-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Health Experiences of Domestically Sex-Trafficked Women in the USA: A Qualitative Study in Rikers Island Jail

Abstract: While sex trafficking in the USA is a significant medical and public health issue, there is sparse data on the healthcare needs of and access for this population. This study was designed to identify experiences of domestically sex-trafficked women regarding healthcare access, reproductive health, and infectious diseases while trafficked. Trafficking survivors incarcerated in New York City's Rikers Island women's jail participated in audio-recorded interviews between July and September 2015. Recordings were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 12 publications
7
86
0
Order By: Relevance
“…19 Additionally, the available research suggests the value of adopting a standardized, evidence-based, trauma-informed approach that incorporates gender, cultural competencies, and survivor input. 6,20 Yet the question remains how best to implement such an approach. Greenbaum et al (2018) applied the Center for Disease Control's Social-Ecological model as a framework for implementing human trafficking prevention strategies for health care professionals.…”
Section: Steps Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Additionally, the available research suggests the value of adopting a standardized, evidence-based, trauma-informed approach that incorporates gender, cultural competencies, and survivor input. 6,20 Yet the question remains how best to implement such an approach. Greenbaum et al (2018) applied the Center for Disease Control's Social-Ecological model as a framework for implementing human trafficking prevention strategies for health care professionals.…”
Section: Steps Forwardmentioning
confidence: 99%
“…Available literature on the medical needs of CSEY, although sparse, has focused on reproductive health and contraception use among adult survivors of commercial sexual exploitation. 5,6,7 A study involving female survivors of commercial sexual exploitation (n=21, age range 18-60 years) detained in a New York City jail described survivors' contraception use while trafficked. Condoms were identified as the most common form of contraception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuum of harmful experiences endured in childhood and throughout the course of exploitation often results in complex trauma that leads to multifarious health care needs. Prior studies have confirmed survivors' significant health-related risks and needs, and documented frequency of using and barriers to accessing health care services (Barnert, Kelly, Ports, et al, 2019;Ijadi-Maghsoodi et al, 2018;Lederer & Wetzel, 2014;Ravi et al, 2017a;Varma et al, 2015). Though health care treatment may be available to youth and young adults affected by CSE, a multitude of structural, environmental, and internal barriers to utilization and engagement (i.e., "buy-in") into treatment remain .…”
Section: Introductionmentioning
confidence: 99%
“…Though health care treatment may be available to youth and young adults affected by CSE, a multitude of structural, environmental, and internal barriers to utilization and engagement (i.e., "buy-in") into treatment remain . As such, the lack of timely care may lead to sequelae such as suicidality, worsening mental and physical health issues, and destructive substance use Greenbaum & Crawford-Jakubiak, 2015;Ijadi-Maghsoodi et al, 2018;Powell et al, 2018;Ravi et al, 2017aRavi et al, , 2017b.…”
Section: Introductionmentioning
confidence: 99%